Election Management Bodies and Election Administration in Nigeria, 2004 – 2019 - Ifedi, Francisca Obiageli; Ezenwankwo, Okwudili Christopher (University of Nigeria Journal of Political Economy, 2023)
This study compared the election management bodies and electoral administrations in Nigeria and Ghana. Through the use of that ex-post-facto research design, the adoption of Marxian theory of the state as its framework, and the deployment of documentary method of data collection, the study investigated the link between the limited autonomy of election management bodies and organizational lapses in the electoral processes as well as the nature of the framework for the conduct of elections and electoral violence in both countries. The study found the limited autonomy of election management bodies to account for electoral violence and organizational lapses in the electoral process more in Nigeria than Ghana. The study also sees the nature of the framework for the conduct of elections to incubate electoral violence more in Nigeria than in Ghana. The study therefore argued that due to the character of the Nigerian state, the performance of electoral management bodies in electoral administration was more susceptible to political manipulations and interferences and, by implication, commanded less public confidence than is the case in Ghana. Among others, the study recommends that the reports of the previous committees on re-structuring the electoral management body and vital aspects of election management in Nigeria be implemented without further delay.